A Morphological Analysis of Inflectional Morphemes in Me Before You Movie - Ni Luh Suryani (Universitas Al-Qolam Malang, 2026)
This study investigates the use of English inflectional morphemes in the spoken dialogues of the two main characters, Louisa Clark and William Traynor, in the film Me Before You. The objectives are to identify the types and functions of inflectional morphemes used, as well as to determine the most dominant form found in the characters’ utterances. Inflectional morphemes, which do not change the basic meaning or word class, provide grammatical information such as tense, number, aspect, possession, and degree of comparison. A qualitative descriptive method was employed, using the film and its transcripts as the primary sources. Data were analyzed using both formal and informal methods. The formal method was used to calculate the frequency of each morpheme, while the informal method was applied to interpret the function of each morpheme in context, based on the theoretical framework by Fromkin et al. The results reveal all eight types of English inflectional morphemes occurred in the data, with the most dominant being the plural marker morpheme -s, which appeared 54 times. The analysis demonstrates that inflectional morphemes are not only essential in shaping grammatical accuracy but also contribute meaningfully to character development and narrative clarity. This research highlights how minor grammatical elements can play a significant role in conveying meaning in naturalistic dialogues. It is expected that this study will offer valuable insight into the application of morphological theory in media discourse and support further research in both linguistics and film studies.